Tourists Perception Toward Kembang Kuning Rural Destination Attractiveness - Weni Retnowati; I Dewa Gede Bisma; Hilmiati Hilmiati; Lalu Adi Permadi (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2022)
This research aims to study the perception of the tourists who visit Kembang Kuning regarding the destination attractiveness. A quantitative method using questionnaire and interview techniques was used in the research. There were 100 participants in which the questionnaire was distributed both offline and online. The result showed that the tourists perceived the Kembang Kuning rural destination as a suitable place to visit in Lombok with good attractiveness. Furthermore, the attractions and the amenities of this destination were perceived as the most looked for by the visitors. The highest perception felt by the tourists is its beautiful natural scenery and intriguing culture. To implement sustainable tourism attractiveness planning in this rural destination, the management must provide additional sanitation facilities, local transport, amenities, and parking lots. In addition, the Kembang Kuning should be creative, and innovative and offer good quality services in other to preserve the differences between this village and others